Patient demographics and psychotropic medication prescribing in Australian general practices: pre- and during COVID-19 pandemic - Kibret, Getiye Dejenu; Kamalakkannan, Abbish; Thomas, Judith; Sezgin, Gorkem; Hardie, Rae-Anne; Pont, Lisa; McGuire, Precious; Pearce, Christopher; Georgiou, Andrew (Journal of primary health care, 2024)
Introduction Mental health conditions, such as depression, anxiety, and psychological distress in the adult population significantly increased during the COVID-19 pandemic. However, the rates of prescribing psychotropic medications in adults during the COVID-19 period have not been well explored. Aim The aim of this study was to examine the association between demographic characteristics and rates of prescribing psychotropic medications to general practice patients during 2018–2022. Methods A total of 154 528 general practice patients aged 20 years and above were included in the study. A mixed effects negative binomial regression model was employed and incidence risk ratios (IRRs) with corresponding 95% confidence interval (CI) are presented to measure the association of demographic characteristics with rates of prescribing psychotropic medication. Results Over half (56.2%) of study subjects were female and 41.4% were aged between 20 and 39 years. Males had lower prescribing rates of antidepressants (IRR = 0.95; 95% CI: 0.94, 0.97) and hypnotics and sedatives (IRR = 0.97; 95% CI: 0.96, 0.99) than females. People in the age group 60+ years (compared with age group 20–39 years) and those in low and middle socio-economic status (SES) categories (compared with high SES) had higher rates of prescribing psychotropic medication. Conclusion Females, people aged 60+ years, and people with low and middle SES had higher prescribing rates of psychotropic medication. A consistent increase in prescribing rates over time, particularly during the COVID-19 pandemic, was observed. It is important that health care planners and policy makers monitor and account for population diversity and equity.